Microbial landscape and immune status in maxillary sinusitis of stomatogenic origin - Kovach, I. V.; Varzhapetian, S. D.; Bunyatyan, Kh. A.; Reyzvikh, O. E.; Babenya, A. A.; Strogonova, T. V.; Ковач, І. В.; Варжапетян, Сурен Діасович; Бунятян, Х. А.; Рейзвих, О. Е.; Бабеня, А. А.; Строгонова, Тетяна Василівна (My University, 2021)
Oroanthral fistula (anastomosis) is an element preventing the restoration of homeostasis in the maxillary sinus due to the constant flow of microbes from the oral cavity. It is also contributes to frequent exacerbations of maxillary sinusitis. Saprophytic grampositive cocci and fungi of the oral cavity are dominating representatives of the microbial flora in the maxillary sinus. As the result of research, we found that in the case of maxillary sinusitis with oroantral fistula fungi made up 25.0% of microbiota, gram-positive bacteria – 41.7%, gram-negative bacteria – 33.3%. Gram-positive cocci from the Staphylococcus genus (Staphylococcus aureus and Staphylococcus epidermidis) and fungi (Candida albicans) comprised the biggest proportion of microbial flora that 33.3% and 16.7%, respectively. Slightly decreased levels of monocytes in venous blood was noted in 69.2% of patients. The average value of total serum IgE in group with oroantal fistula was 226.2 (70.4) IU/ml, the result exceeded normal limits almost in 2.26 times. Large circulating immune complexes (CICs) were normal in all patients in the group with iatrogenic maxillary sinusitis. The average lavels of small size CICs was 170.2 (4.23) ОU, which is in 1.06 times higher the upper limit of the norm (160 ОU). Elevated levels of total Ig E in serum of patients with oroanthral fistula indicates allergic sensitization. The detection of increased levels of CICs with small and medium sizes in serum may indicate a susceptibility of this category of patients to the development of immunopathological reactions. Ороантральне співустя є елементом, який перешкоджає відновленню гомеостазу у верхньощелепному синусі через постійний потік мікробіоти з порожнини рота та спричиняє часте загострення синуситу. Проведене нами дослідження дозволило встановити, що сапрофітні коки та гриби з порожнини рота становлять більшу частину мікробіоти верхньощелепної пазухи в пацієнтів з ороантральним сполученням. При цьому гриби становлять 25,0%, грампозитивні бактерії – 41,7%, грамнегативні бактерії – 33,3%. Переважають грампозитивні коки роду Staphylococcus spp.: Staphylococcus aureus та Staphylococcus epidermidis (33,3%). Другими за поширеністю були гриби C. albicans (16,7%). Ми виявили помірне підвищення моноцитів у крові 69,2% пацієнтів, що може бути пов’язано з початком стадії гострого запалення. Наявність грибів свідчить про можливе порушення місцевого імунітету. Середній рівень загального IgЕ сироватки крові в досліджуваній групі становив 226,2 (70,4) МО/мл та перевищував норму майже в 2,26 раза. Рівні великих циркулюючих імунних комплексів (ЦІК) були нормальними у всіх пацієнтів у групі з оронтральною фістулою. Середнє значення малих ЦІК становило 170,2 (4,23) оптичних одиниць (ОО), що в 1,06 раза перевищувало верхню границю норми (160 ОО). Рівень загального сироваткового Ig Е вказує на алергічну сенсибілізацію організму. Виявлене підвищення рівня ЦІК малих та середніх розмірів у сироватці може свідчити про сприйнятливість цієї категорії хворих до розвитку імунопатологічних реакцій.
Мікробний пейзаж та імунний статус при верхньощелепному синуситі стоматологічного походження
Keywords: stomatogenic maxillary sinusitis; microbiota; iatrogenic sinusitis; the etiopathogenesis of sinusitis; differential diagnostics; стоматогенний верхньощелепний синусит; мікробіота; ятрогенний синусит; диференціальна діагностика